Leishmaniose visceral na região Nordeste: distribuição espaço-temporal de casos e óbitos - NOGUEIRA, Josilma Silva (2020)
INTRODUCTION: Visceral Leishmaniasis (VL) is a serious public health problem with worldwide distribution. It is currently among the seven endemic diseases considered a priority for health actions in the world, being included in the list of neglected tropical diseases. VL has a wide geographic distribution of human cases in Brazil, with the highest number of cases registered in the Northeast region, followed by the Southeast, North, Midwest and South. OBJECTIVE: To analyze the trend and spatial-temporal distribution of Visceral Leishmaniasis in the Northeast region. METHOD: This is an ecological study of the trend and spatial pattern of cases and deaths from VL that occurred in the Northeast region, notified in the Information System for Notifiable Diseases of the Ministry of Health of Brazil (SINAN/MS) and in the Mortality Information (SIM/MS) in the period from 2013 to 2019. To study the incidence trend and mortality rate, a Prais-Winsten generalized linear regression model was used. For the study of spatial analysis, the incidence and lethality rates of VL in the region were analyzed from 2013 to 2019, for each year, and the adjusted incidence was calculated by the local empirical Bayesian model. To observe the existence of spatial autocorrelation, the Global and Local Moran Indexes were calculated to delimit areas of higher and lower risk for illness and death from VL in the Northeast region. Statistical analyzes were performed using Stata® version 14.0 and GeoDa version 1.14.1 software. All maps were built in QGIS 3.22.3 software. RESULTS: The trend of VL incidence was decreasing in Piauí, Ceará and Bahia, remaining stable in the other states of the region. There was a decrease in the lethality trend only in Paraíba, remaining stable in the other states. The spatial analysis of cases and deaths showed a wide distribution of the disease, but with a greater agglomeration of high risk for illness in those states where the incidence has historically been high. CONCLUSION: VL was stable in the northeast region, but with an increased potential for lethality. The present study, by identifying VL risk states and clusters, can contribute to the elaboration and strengthening of more specific control actions.